2013
DOI: 10.1002/jbio.201300036
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the noncentrosymmetric structural organization of tendon with Interferometric Second Harmonic Generation microscopy

Abstract: Journal of BIOPHOTONICSWe report the imaging of tendon with Interferometric Second Harmonic Generation microscopy. We observe that the noncentrosymmetric structural organization can be maintained along the fibrillar axis over more than 150 mm, while in the transverse direction it is $1-15 mm. Those results are explained by modeling tendon as a heterogeneous distribution of noncentrosymmetric nanocylinders (collagen fibrils) oriented along the fibrillar axis. The preservation of the noncentrosymmetric structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 28 publications
5
36
0
Order By: Relevance
“…This provides a relative value for the phase (φ exp ) at all the pixels in the image. Images obtained previously in a periodically poled lithium niobate crystal and in rat tail tendon tissues have confirmed that ISHG microscopy allows imaging of the relative orientation between noncentrosymmetric domains [35].…”
Section: Methodssupporting
confidence: 65%
“…This provides a relative value for the phase (φ exp ) at all the pixels in the image. Images obtained previously in a periodically poled lithium niobate crystal and in rat tail tendon tissues have confirmed that ISHG microscopy allows imaging of the relative orientation between noncentrosymmetric domains [35].…”
Section: Methodssupporting
confidence: 65%
“…For SHG of collagen fibers, the fiber arrangement, the polarization and phase of the emitted signal provides insight into the orientation and ordering of the fibers (Figure 2). Interferometric SHG imaging is used to determine the polarity of domains of collagen fibrils, revealing that the observed SHG signal is due to domains of partially ordered collagen fibrils (see Figure 2B) [34]. Polarization sensitive SHG enables visualization of the fiber direction.…”
Section: Methodsmentioning
confidence: 99%
“…(B) Interferometric SHG imaging is used to determine the polarity of collagen fibers and fibrils, revealing that the observed SHG signal is due to domains of partially ordered collagen fibrils. Adjacent fibers may have opposite polarity (green: negative polarity, red: positive polarity) [34]. (C) Polarization sensitive SHG enables visualization of the fiber direction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations